2010
DOI: 10.1007/s10714-010-1069-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuous matter creation and the acceleration of the universe: the growth of density fluctuations

Abstract: Cosmologies including continuous matter creation are able to reproduce the main properties of the standard ΛCDM model, in particular in cases where the particle and entropy production rates are equal. These specific models, characterized by a mass density equal to the critical value, behave like the standard ΛCDM model at early times whereas their late evolution is similar to the steady-state cosmology. The maximum amplitude of density fluctuations in these models depends on the adopted creation rate, related … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
3
18
0
Order By: Relevance
“…Taking into account thatṅ n = Γ − 3H, equation 18 is finally expressed as equation 19, which matches the one obtained by other authors [23]…”
Section: Specific Entropy Is Constantsupporting
confidence: 85%
“…Taking into account thatṅ n = Γ − 3H, equation 18 is finally expressed as equation 19, which matches the one obtained by other authors [23]…”
Section: Specific Entropy Is Constantsupporting
confidence: 85%
“…In conclusion, we have shown that the Newtonian analysis performed by de Roany and Pacheco [1] fails when trying to recover the background (zero order) relativistic model proposed in Ref. [2].…”
mentioning
confidence: 72%
“…At this point, we stress that the original notation of [2] will be adopted. In the notation of [1], α is represented by Ω v .…”
mentioning
confidence: 99%
“…Instead we can say that we are the result of an initial small bang, just after inflation of an initial fluctuation, an initial quantum black hole whose inflation a little later decelerated. But this deceleration was overcome by the push of the creation pressure, the continuous creation of matter [2], [3], [4] and [5]. As we will see, most physicals properties of the universe are subject to this increase with time.…”
Section: Introductionmentioning
confidence: 99%